1983
DOI: 10.1083/jcb.97.5.1396
|View full text |Cite
|
Sign up to set email alerts
|

Aggregates of acetylcholine receptors are associated with plaques of a basal lamina heparan sulfate proteoglycan on the surface of skeletal muscle fibers.

Abstract: Hybridoma techniques have been used to generate monoclonal antibodies to an antigen concentrated in the basal lamina at the Xenopus laevis neuromuscular junction. The antibodies selectively precipitate a high molecular weight heparan sulfate proteoglycan from conditioned medium of muscle cultures grown in the presence of [3~S]methionine or [35S]-sulfate. Electron microscope autoradiography of adult X. laevis muscle fibers exposed to 12Sl-labeled antibody confirms that the antigen is localized within the basal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
2
1

Year Published

1984
1984
2000
2000

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(125 citation statements)
references
References 80 publications
5
117
2
1
Order By: Relevance
“…4). Besides AChRs, several muscle components have been implicated in the generation of NARPs, including components of the extracellular matrix (Burden et al, 1979;Anderson and Fambrough, 1983;Vogel et al, 1983;McMahan and Slater, 1984;Fallon et al, 1985) and the cytoskeletal system (Bloch, 1986;Froehner, 1986;Peng and Poo, 1986). The supply of any of these might limit the capacity of muscle cells to generate NARPs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4). Besides AChRs, several muscle components have been implicated in the generation of NARPs, including components of the extracellular matrix (Burden et al, 1979;Anderson and Fambrough, 1983;Vogel et al, 1983;McMahan and Slater, 1984;Fallon et al, 1985) and the cytoskeletal system (Bloch, 1986;Froehner, 1986;Peng and Poo, 1986). The supply of any of these might limit the capacity of muscle cells to generate NARPs.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, these 2 synaptic specializations may develop independently of each other, but with time the incidence of spatial alignment increases (Bixby and Reichardt, 1985). Components of the synaptic basal lamina have been implicated in the development of both these specializations (Sanes et al, 1978;Burden et al, 1979;Anderson and Fambrough, 1983;Vogel et al, 1983;McMahan and Slater, 1984;Fallon et al, 1985;Anderson, 1986).…”
mentioning
confidence: 99%
“…La stimulation du muscle squelettique adulte provoque une augmentation très importante de la concentration en GMPc musculaire (Nestler et al, 1978). De même, l'addition de GMPc à des cultures de muscle mime les effets de l'activité sur l'AChE synaptique (Rubin et al, 1980 Fambrough, 1983 ;Sanes et Chiu, 1983 (1983,1984), Nitkin etal. (1983Nitkin etal.…”
Section: A) Propriétés Des Fibres Musculairesunclassified
“…These enzymes selectively degrade the different classes of glycosaminoglycan side chains that characterize each species of proteoglycan. Control experiments demonstrated that whereas commercial preparations of hyaluronidase and keratanase exhibited detectable levels of protease contamination, the chondroitinase ABC and two separate heparinase preparations did not (2). In experiments where [35S]sulfate-labeled immunoprecipitates were treated with the various enzymes before electrophoretic analysis (Fig.…”
Section: Antigen-31--lamininmentioning
confidence: 99%